KORELASI SIKAP TERHADAP PEMBELAJARAN FISIKA DAN HASIL BELAJAR FISIKA SISWA KELAS XI IPA MAN TALUK KUANTAN - Deski Permadi; Zulirfan '; M. Nor ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of the study is to identify the correlation between the students attitude toward physics learning and student’s achievement class XI science of MAN Taluk Kuantan at 2015/2016 academic year. There wear 78 students participated as respondence in this research. The instruments of this study was questioner of students attitude toward physics learning. The study found that there are a positive and significant correlation between the students attitude toward physics learning and students achievement of MAN Taluk Kuantan. This study identified that there are 51% of negative attitudes respondence showed. We also identified the students achievement were low category.Keywords: study result, learning attitude, physics learning, correlation..